2022
DOI: 10.3389/fpsyt.2022.925823
|View full text |Cite
|
Sign up to set email alerts
|

Decreased resting-state functional connectivity of the habenula-cerebellar in a major depressive disorder

Abstract: BackgroundIn animal experiments, the habenula and septal nuclei are known as the key brain areas of depression. However, there are few magnetic resonance imaging (MRI) studies on the functional connectivity between these areas and the subcortical areas in humans with major depression. We aimed to investigate the difference in resting-state functional connectivity (RSFC) among the major regions of interest (ROI) in the subcortical areas, including both the habenula and septal nuclei.MethodsWe performed the seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Indeed, both left and right Hb activation has been shown to increase in healthy controls when exposed to a negative outcome (95, 96). However, those with a diagnosis of MDD recorded either no or attenuated change in Hb activation following exposure to the same negative stimuli (95, 96). Similarly, in an error prediction learning task, adolescents with MDD exhibited a reduction in negative related signalling in the Hb when compared to controls (98).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, both left and right Hb activation has been shown to increase in healthy controls when exposed to a negative outcome (95, 96). However, those with a diagnosis of MDD recorded either no or attenuated change in Hb activation following exposure to the same negative stimuli (95, 96). Similarly, in an error prediction learning task, adolescents with MDD exhibited a reduction in negative related signalling in the Hb when compared to controls (98).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the Hb signals negative stimuli, it is expected that Hb activity would increase in response to a negative outcome. Indeed, both left and right Hb activation has been shown to increase in healthy controls when exposed to a negative outcome (95, 96). However, those with a diagnosis of MDD recorded either no or attenuated change in Hb activation following exposure to the same negative stimuli (95, 96).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, asymmetry of functional connectivity of the human Hb was found for the first time through fMRI 42 . Studies in humans using resting‐state fMRI have shown that the Hb has extensive functional connections with areas such as the VTA, SN, RN, periaqueductal gray, medial prefrontal cortex (mPFC), dorsolateral prefrontal cortex, and cerebellum (Table S2 in the Supplemental Material) 40,41,43–55 . In a previous study, the bilateral Hb in the 15 patients with schizophrenia showed a markedly stronger resting‐state functional connectivity (RSFC) than did that in the 16 healthy controls (Fig.…”
Section: Fmri In the Hbmentioning
confidence: 98%